Characterisation and targeting of stem cells in myelodysplastic syndromes - Chowdhury, O (2013)
Understanding which cells within a cancer are responsible for its initiation and propagation is vital if we are to achieve cure. If cancer stem cells are the only population able to sustain a tumour long term, designing therapeutic strategies to target this population will give medical science the best chance of long-term cure. Significant controversy remains over the existence of cancer stem cells, predominantly due to the lack of a sensitive human cancer stem cell assay. This thesis investigates whether two haematological malignancies, myelodysplastic syndromes (MDS) and chronic myelomonocytic leukaemia (CMML) can only be driven by rare and distinct cancer stem cells. We have demonstrated that low and intermediate-1 risk MDS is driven solely by the stem cell (Lin- CD34+ CD38- CD90+ CD45RA-) by developing a novel genetic approach, tracing all somatic mutations and karyotypic abnormalities back to this population. Prior to this study, very little was known about the clonal architecture of CMML. By performing detailed phenotypic, functional, molecular and genetic analysis of patients with CMML, we were able to demonstrate that the most likely candidate driver cell in these patients was also the stem cell rather than any of the down-stream progenitors. Currently, effective therapeutic strategies for MDS or CMML are very limited. Allogeneic stem cell transplantation is the only potential cure and not suitable for most patients. Cancer stem cells, including MDS stem cells are known to be highly quiescent and selectively resistant to therapy. Having demonstrated that both MDS and CMML were driven by stem cells, we developed a novel therapeutic targeting strategy. Using the thrombopoietin receptor agonist, Romiplostim, we were able to activate stem cells and enhance their subsequent sensitivity to chemotherapy dramatically. This approach may facilitate improved remission rates and prevent cancer stem cell driven relapse in many diseases.